Respostas

2014-01-28T08:36:19-02:00
4x²-64=0                      8x²+6x=0
x²=64/4                        x(8x+6)= 0            
x²=16                           x=0
s-4,4                            8x+6=0
                                     x=-6/-8
                                      x= 3/4
                                           S=0,3/4


(X+5)(X-6)=51-X
X²-6X+5X-30=51-X
X²-81=0
X²= 81
S=+9,-9

3X²-75=0
X²=75/3  25
 S=5,-5

X²+2=2
X²+2-2=0
S=0

X²+3X(X-12)=0
X²+3X²-36X=0
4X²-36X=0
X(4X-36)=0
X=0
4X-36=0
X=36/4
X=9
S=0,9
1 5 1